Carbon stock and sequestration analysis of high-density plantation in Neyveli, Tamil Nadu - Sugumaran, MP; Goveanthan, AS; Porkodi, G; Gayathry, G; Kalaichelvi, K; Bharathi, KK; Kiruba M, M; Natarajan, K (Plant Science Today, 2026)
Akira Miyawaki developed a unique reforestation method (the Miyawaki method) in Japan during the 1980s, aimed at restoring native ecosystems, conserving natural habitats, improving disaster resilience and reducing CO2 emissions. This study evaluates the growth performance of tree species planted using the Miyawaki technique at New Thermal Power Station II, Neyveli Lignite Corporation India Limited (NLCIL), Neyveli, where afforestation was completed in 2022. Using a high-density planting strategy, 50 tree species were planted, including timber-species, fruit-bearing trees and ornamental species. Biometric parameters such as plant height and basal diameter were recorded, along with biochemical traits including crude protein, crude fiber and crude fat. Carbon biomass was calculated for each tree and CO₂ sequestration by individual trees was measured to assess their carbon capture potential. The tree species Albizzia lebbeck (14.03 kg tree-1), Diospyros ebenum (13.25 kg tree-1), Terminalia arjuna (12.73 kg tree-1) and Pithecellobium dulce (10.97 kg tree-1) exhibited higher CO₂ equivalents than other species. The Miyawaki plantation alter the local microclimate, with a moderate cooling effect observed during winter, reducing air temperatures to 31.25 °C compared to 32.54 °C in the open area. Relative humidity increased to 59.13 % within the plantation compared to 48.79 % in the open area. The plantation also led to marginal increase in soil organic carbon content. Miyawaki plantations demonstrated positive effects on microclimatic regulation and ecosystem functioning. The findings of this study help identify tree species with superior performance under Miyawaki planting conditions, providing useful guidance for future afforestation programs in areas with comparable climatic and ecological settings.